Analisis Faktor Faktor yang Mempengaruhi Non Performing Loan pada Bank Pemerintah Daerah di Indonesia - Permata, Yoeni Reza; Zoraya, Intan (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
In this study, researchers observed non-performing loans for the 2019-2022 period at 23 local government banks in Indonesia. This study uses eight independent variables: return on equity, firm size, GDP, equity ratio, capital adequacy ratio, loan-to-deposit ratio, net interest margin, inflation, and the composite stock price index. Meanwhile, bad debts are the dependent variable used. The results of the study using multiple linear regression analysis show that non-performing loans are influenced by capital adequacy ratio, net interest margin, return on equity, and company size. Non-performing loans are not affected by loan to deposit ratio, inflation, GDP, or the composite stock price index.